ANXIETY, DEPRESSION, MACRONUTRIENT INTAKE AND NUTRITIONAL STATUS OF CANCER SURVIVORS LIVING IN SHELTER HOUSES AFTER CHEMOTHERAPY: A CROSS-SECTIONAL STUDY - Nadya Ika Indryani; Rachma Purwanti; Ani Margawati; Choirun Nissa (Media Gizi Indonesia, 2022)
Depression and anxiety are common in cancer patients due to metabolism alteration and the side effects of chemotherapy. These mental health problems could be even worse in patients with low economy status and living in shelter houses. The aim of the research was to analyze the relationship of anxiety, depression, and macronutrient intake with nutritional status in cancer survivors undergoing chemotherapy at shelter houses. A total of 42 cancer patients aged 40-60 years old at shelter houses was recruited using consecutive sampling under a cross-sectional study design. Anxiety and depression data were taken using the Hospital Anxiety and Depression Scale (HADS) questionnaire, while energy, protein, fat, and carbohydrate data intakes were using Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). The nutritional status data was examined based on Mid Upper Arm Circumference (MUAC). The data were analyzed using Pearson and Rank Spearman tests. Results of the study indicate that there were significant relationships between energy (p=0.040; r=0.318) and fat (p=0.001; r=0.490) with nutritional status. However, there was no relationship between anxiety and depression with macro-nutrient adequacy; also protein and carbohydrate intake with nutritional status. Anxiety and depression with nutritional also did not relate as evidenced by the value (p>0.05). To sum up, although there were no correlations between anxiety and depression with nutritional status, correlations occurred between energy and fat with nutritional status. Further research is suggested to analyze variables underlying anxiety and depression such as family support, stage, duration of diagnosis and frequency of chemotherapy so that these variables can be controlled.